Building Palliative Care Capacity for Generalist Providers in the Community: Results From the Capaciti Pilot Education Program. (July 2023) - Seow, Hsien; Bainbridge, Daryl; Stajduhar, Kelli; Marshall, Denise; Howard, Michelle; Brouwers, Melissa; Barwich, Doris; Burge, Fred; Kelley, Mary Lou
Objective: Primary care providers play an important role in providing early palliative care, however they often lack practical supports to operationalize this approach in practice. CAPACITI is a virtual training program aimed at providing practical tips, strategies, and action plans to help primary care providers offer an early palliative approach to care. The CAPACITI pilot program consisted of 10 facilitated, monthly training sessions, covering identification and assessment, communication, and engaging caregivers and specialists. We present the findings of an evaluation of the pilot program.Method: We conducted a single cohort study of primary care providers who participated in CAPACITI. Study outcomes were the change in the percentage of caseload reported as requiring palliative care and improved confidence in competencies measured on a 20-item, study-created survey. Pre and post survey data were analyzed using paired t-tests.Results: Twenty-two teams representing 127 care providers (including 36 physicians and 28 Nurse Practitioners) completed CAPACITI. Paired comparisons showed a moderate improvement in confidence across the competencies covered (.6 to 1.3 mean improvement across items using seven-point scales, all P < .05). Pre-CAPACITI, clinician prescribers ( N = 32) identified a mean of 1.2% of their caseload requiring a palliative approach to care, which increased to 1.6% post-program ( P = .02). Said differently, the total group of paired clinician prescribers identified 338 patients as requiring palliative care in their caseloads at baseline vs 482 patients following the intervention, for an overall increase of 144 patients in their collective caseloads.Conclusion: CAPACITI improved self-assessed palliative care identification and provider confidence in core competencies. The program demonstrated potential for building palliative care capacity in primary care teams.